IMPLEMENTASI MODEL PEMBELAJARAN SNOWBALL THROWING DALAM UPAYA MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR PEMELIHARAAN CHASIS SEPEDA MOTOR SISWA TBSM SMKN 2 PAMEKASAN - Emdi Ramadana putra; Rico Andhika Putra; Nurul Laili Sa'adah (Journal of Automotive Vocational Education (JAVED), 2024)
Many teachers at SMKN 2 Pamekasan still use the conventional learning model or the more familiar lecture model. This conventional learning model causes students to be inactive in the classroom because learning is focused on the teacher so that the impact is felt by students in decreasing learning achievement. So that this phenomenon does not continue, researchers will implement the snowball throwing learning model in an effort to increase student activity and learning achievement at SMKN 2 Pamekasan, especially the Motorcycle Business Engineering (TBSM) skills program. This research is a classroom action research with 29 students in class XI A TBSM SMKN 2 Pamekasan, sample selection using purposive sampling technique. This classroom action research consisted of 3 cycles which resulted in data increasing activity by 24.07% and learning achievement by 58.48%.